Criminal procedure in Nigeria : Law and Practice - Doherty, Oluwatoyin (Great Britain Blackstone press Ltd., 1990)
This is the first book to attempt to set down the law of Criminal Procedure in Nigeria as a whole. It commences with a delimitation of the perimeters of criminal procedure. It discourses the composition of courts, the role of council in criminal litigation and courts vested with criminal jurisdiction in Nigeria. It considers matters ancillary to criminal proceedings such as summonses, arrest, searches and bail. It deals with the institution of criminal proceedings, if any on the institution of such proceedings. the intricate rules governing the drafting of charges are unravelled and made easy to understand.
includes index
aau, 01/08/2022
Loan
Keywords: criminal procedure; law and practice